The Relationship Between Medication Adherence, Antipsychotic Side Effects, and Quality of Life in Schizophrenia Patients: An Evaluation Using Mars10, Gass, and SQLS - Mariance Trisnawati; Sylvia Rizki Prima (Eduvest - Journal of Universal Studies, 2025)
This study aimed to analyze the relationship between medication adherence, antipsychotic side effects and quality of life in schizophrenic patients. A total of 263 respondents participated in this study using three validated instruments: the Medication Adherence Rating Scale (MARS-10), the Glasgow Antipsychotic Side-effect Scale (GASS), and the Schizophrenia Quality of Life Scale (SQLS). The results of the analysis showed a very significant positive correlation between medication adherence and patient quality of life (r = 0.808; p = 0.000). In contrast, no significant association was found between antipsychotic side effects and adherence (r = -0.003; p = 0.956) or quality of life (r = -0.028; p = 0.649). The three instruments used showed high reliability with Cronbach's Alpha values of 0.941 (MARS-10), 0.970 (GASS), and 0.981 (SQLS), respectively. These findings confirm the importance of interventions aimed at improving medication adherence as a key strategy in improving the quality of life of schizophrenic patients. Further research recommends for future patient-centered approaches, ongoing education, strong family involvement and therapeutic relationships, as well as the need for social support from other psychosocial factors.